Changes in Rainfall Pattern in Bengawan Solo Sub-Watershed - Muchamad Wahyu Trinugroho; Sigit Supadmo Arif; Sahid Susanto; Bayu Dwi Apri Nugroho; Abi Prabowo (Universitas Sebelas Maret, 2022)
Rainfed farming is vulnerable to climate variability, which changes rainfall patterns. Rainfall variability disrupts rainfed rice cultivation because a change in rainfall will affect the rice crop calendar. An analysis of long-term trends over a specific area is required to understand rainfall variability. The aim of this study was to assess climate variability in terms of rainfall magnitude and frequency by analyzing spatial and temporal rainfall trends in Bengawan Solo Sub-Watershed as well as the rainfed rice production. Daily rainfall data from 10 rain gauge stations over the sub-watershed area from the years 1975 to 2020 were used. The data was managed and collected by the Bengawan Solo Watershed authority. Pearson, Mann-Kendall, and Sen’s Slope tests were applied to assess the recorded data correlation, rainfall trends, and magnitude of trends into annual, monthly, and 10-day. The findings of the study indicated the spatial and temporal inhomogeneous rainfall pattern for all locations for 10-day, monthly and annual patterns. The mountainous regions at Tawang Mangu and Ngrambe stations tend to experience an upward trend (positive magnitude), while the coastal regions at Nglirip and Bojonegoro stations have a downward trend(negative magnitude). Those trends also confirmed that coastal regions would be drier than mountainous regions in the future. Understanding this rainfall trend can assist with rainfed farming strategic planning.